2016
DOI: 10.1017/cjn.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Incidence of Frontotemporal Dementia: a Systematic Review

Abstract: Background: Population-based prevalence and incidence studies are essential for understanding the burden of frontotemporal dementia (FTD). Methods: The MEDLINE and EMBASE databases were searched to identify population-based publications from 1985 to 2012, addressing the incidence and/or prevalence of FTD. References of included articles and prior systematic reviews were searched for additional studies. Two reviewers screened all abstracts and full-text reviews, abstracted data and performed quality assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(139 citation statements)
references
References 62 publications
(199 reference statements)
4
133
0
2
Order By: Relevance
“…These statements indicate a disapproval of the subtle categorization and the associated restrictions that seemed to unite the patient group. Uneasiness related to the frames of care may be of particular relevance with regard to patients with FTD because these patients are often quite young [1]. In a study on how relatives of people with frontotemporal dementia experience the illness, all of the participants found that they needed to be assertive to gain access to what they considered appropriate services.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These statements indicate a disapproval of the subtle categorization and the associated restrictions that seemed to unite the patient group. Uneasiness related to the frames of care may be of particular relevance with regard to patients with FTD because these patients are often quite young [1]. In a study on how relatives of people with frontotemporal dementia experience the illness, all of the participants found that they needed to be assertive to gain access to what they considered appropriate services.…”
Section: Discussionmentioning
confidence: 99%
“…Frontotemporal dementia (FTD) is a pathologically and clinically heterogeneous group of non-Alzheimer neurodegenerative dementias [1]. People with neuronal degeneration in frontal and temporal lobes demonstrate a decline in social conduct, and/or language aphasias, apathy, and loss of insight that is gradual and progressive [1, 2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…No estudo de Takada et al (2003), a DFT foi diagnosticada em 5,1% dos pacientes atendidos no São descritas na literatura três condições principais na DFT: DFTvc (Rascovsky et al, 2011;Hornberger et al, 2012), APPvs, APPvnf, APPvl (Hodges et al, 2001;Boxer et al, 2005;Gorno-Tempini et al, 2011).Em estudo de revisão, Hogan et al (2016) documentaram que há uma média de 2,7% de pacientes com DFTvc em estudos de prevalência de demência no mundo. Os dados indicaram que houve predominância do sexo masculino (52,5%).…”
Section: Demência Frontotemporal (Dft) E Seus Subtipos: Epidemiologiaunclassified